Morphological and swelling behavior of cellulose nanofiber (CNF)/poly(vinyl alcohol) (PVA) hydrogels: poly(ethylene glycol) (PEG) as porogen - Xu, Zhaoyang; Li, Jianyu; Zhou, Huan; Jiang, Xiangdong; Yang, Chuang; Wang, Fei; Pan, Yuanyuan; Li, Nana; Li, Xiaoyan; Shi, Lina; Shi, Xiaomei (RSC advances, 2016)
Novel interconnected PVA-based hydrogels with controlled porous structure prepared by freezing/thawing and porogen technique are presented in this study. Three types of poly(ethylene glycol) (PEG), with various molecular weights, have been used as porogens. Cellulose nanofiber (CNF) was incorporated into PEG-modified hydrogels as the reinforcement. The influences of PEG and CNF on the microstructure, swelling behavior and thermal properties of hydrogels were investigated. The results indicated that the porosity of hydrogels was significantly increased with PEG incorporated, and the pore size increased as the increasing of PEG molecular weight. The CNF greatly improved the hydrogel connectivity. The CNF further enhanced the swelling property on the basis of the excellent improvement effect of PEG. In addition, significantly increased thermal stability was obtained with the CNF/PEG-modified hydrogels in comparison with the pure PVA hydrogels. The low cost, nontoxic, high-performance and biocompatible hydrogels may have a promising application in biomedical fields. Novel interconnected PVA-based hydrogels with controlled porous structure prepared by freezing/thawing and porogen technique are presented in this study.